2006
DOI: 10.1002/ppul.20383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of complicated pneumococcal pneumonia in a pediatric population

Abstract: The incidence of complicated pneumonia caused by S. pneumoniae is reported to be increasing. This increase may be related to host susceptibility and/or pathogen virulence. The objective of this study was to evaluate clinical and laboratory characteristics associated with complicated pneumococcal pneumonia, and to identify risk factors associated with prolonged fever and hospitalization. The study involved reviewing the records of all children who were hospitalized in four major hospitals in Jerusalem with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
54
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 37 publications
10
54
1
1
Order By: Relevance
“…The age range and demographic features of the present patients are similar to other published studies of children with complicated pneumonia [14][15][16]. Most children had developed symptoms of fever and cough for f1 week prior to their hospitalisation, indicating that the parenchymal damage in NP occurs rapidly.…”
Section: Discussionsupporting
confidence: 70%
“…The age range and demographic features of the present patients are similar to other published studies of children with complicated pneumonia [14][15][16]. Most children had developed symptoms of fever and cough for f1 week prior to their hospitalisation, indicating that the parenchymal damage in NP occurs rapidly.…”
Section: Discussionsupporting
confidence: 70%
“…Other authors have reported the risk of complications in such cases, given that a timely diagnosis can prevent progression to pleural effusion in patients with CAP. (14,17,19,(27)(28)(29) A delay in the initiation of antibiotic therapy, an inappropriate choice of antibiotics, and the use of lower than recommended doses of antibiotics can have a negative impact on the clinical course of bacterial pneumonia. However, there is a concern about the incorrect indication of penicillins in viral processes; this is a commonplace practice in emergency rooms and can lead to increased bacterial resistance to the antibiotics that are widely used in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…El neumatocele es una complicación poco reportada de la neumonía 1 . Es una formación adquirida de contenido aéreo de paredes delgadas formadas por el parénquima pulmonar adyacente.…”
Section: Introductionunclassified